Cultura organizacional nos processos de inovação: um estudo em uma instituição de ensino pública - Batista, Ricardo Menezes (2020)
Organizational culture and innovation are present in educational institutions today. The presence of an organizational culture and innovative postures are strategic elements for organizations that arouse interest in researching these themes. A current phenomenon, which has aroused different interest in innovation in organizations, is the Covid-19 pandemic. In this light, this research was developed with the general objective of analyzing the influence of organizational culture in the innovation processes at the Federal Institute of Science and Technology Education of Santa Catarina (IFSC). For the development of the study, a Framework was built by combining the model of Hosftede (1980) and the model of the Globe Project, using seven dimensions. As for the research methodology, it is highlighted that the adopted paradigm was interpretative, a pragmatic analysis with a qualitative approach. The data were collected through primary sources, semi-structured interviews with the course coordinators of the Gaspar campus and the pro-rectors. In addition to primary sources, secondary sources of data collection were sought, for which the institutional development plan (IDP), the IFSC website and management reports were used. The result of the research pointed out that the analyzed institution is an innovative institution in the national scenario of public education, presenting, in its organizational culture, characteristics of the dimensions of Hofstede (1980) and the Globe Project (2002), such as individualism / collectivism, collectivism of gripo, distance from power, aversion to uncertainty, orientation towards the future, human orientation and group collectivism. The research also allowed reflections on the institution's organizational culture, the temporality of development of its organizational processes and the perception of elements that contribute to innovation.